2010
DOI: 10.1038/oby.2010.57
|View full text |Cite
|
Sign up to set email alerts
|

Food‐Related Odor Probes of Brain Reward Circuits During Hunger: A Pilot fMRI Study

Abstract: Food aromas can be powerful appetitive cues in the natural environment. Although several studies have examined the cerebral responses to food images, none have used naturalistic food aromas to study obesity. Ten individuals (five normal‐weight and five obese) were recruited to undergo 24 h of food deprivation. Subjects were then imaged on a 3T Siemens Trio‐Tim scanner (Siemens, Erlangen, Germany) while smelling four food‐related odors (FRO; two sweet odors and two fat‐related) and four “nonappetitive odors” (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 49 publications
6
93
0
Order By: Relevance
“…Indeed, differences in processing of odors related to food and non-food are observable with modern neuroimaging techniques. Odors of the desired foods induced a significantly larger BOLD (blood oxygenation level-dependent) response than odors unrelated to food in the reward-processing areas (such as the ventral tegmental area, ventral striatum, and medial frontal cortex) of ten hungry women (five of which were obese and five were lean) (Bragulat et al 2010). After stimulation with sweet food odors (chocolate cookie and strawberry/cream) and sweet nonfood odors (rose and lilac), the perceived sweetness of the food odors correlated significantly with the activity in the left insula but not the perceived sweetness of the flower odors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, differences in processing of odors related to food and non-food are observable with modern neuroimaging techniques. Odors of the desired foods induced a significantly larger BOLD (blood oxygenation level-dependent) response than odors unrelated to food in the reward-processing areas (such as the ventral tegmental area, ventral striatum, and medial frontal cortex) of ten hungry women (five of which were obese and five were lean) (Bragulat et al 2010). After stimulation with sweet food odors (chocolate cookie and strawberry/cream) and sweet nonfood odors (rose and lilac), the perceived sweetness of the food odors correlated significantly with the activity in the left insula but not the perceived sweetness of the flower odors.…”
Section: Introductionmentioning
confidence: 99%
“…van der Laan et al found that the most common brain regions activated in response to viewing food pictures were the bilateral posterior fusiform gyrus, the left middle insula, and the left lateral OFC. In research using non-picture cues, food-related words (BarrosLoscertales et al, 2012;Pelchat, Johnson, Chan, Valdez, & Ragland, 2004) and food-related odors (Bragulat et al, 2010;Eiler, Dzemidzic, Case, Considine, & Kareken, 2012) activated similar brain regions, demonstrating that a common distributed network processes food cues across different input modalities (pictures, words, and odors). In each case, food cues appear to activate the same ventral reward pathway, suggesting that different cues produce similar anticipatory responses.…”
Section: The Neural Network Associated With Processing Food Cues (Cormentioning
confidence: 99%
“…Specifically, obese compared with lean individuals have shown greater responsivity in reward-related regions (striatum, pallidum, amygdala, and orbitofrontal cortex) and attention regions (visual and anterior cingulate cortices) to appetizing food images (1)(2)(3)(4)(5), anticipated palatable food intake (6,7), and food odors (8). Obese compared with lean humans have also shown greater activation in the primary gustatory cortex (anterior insula and frontal operculum) and in oral somatosensory regions (postcentral gyrus and parietal operculum) during exposure to appetizing food images (2,5) and anticipated palatable food intake (6,7).…”
Section: Introductionmentioning
confidence: 99%